Topic Modeling on Online News.Portal Using Latent Dirichlet Allocation (LDA) - Mohammad Rezza Fahlevvi; Azhari SN (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2022)
The amount of News displayed on online news portals. Often does not indicate the topic being discussed, but the News can be read and analyzed. You can find the main issues and trends in the News being discussed. It would be best if you had a quick and efficient way to find trending topics in the News. One of the methods that can be used to solve this problem is topic modeling.